2011
DOI: 10.1111/j.1574-695x.2011.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bordetella holmesii isolates from patients with pertussis-like illness in the Netherlands

Abstract: Bordetella holmesii is a recently described human pathogen mainly isolated from blood. However, in the US and Canada, B. holmesii has also been cultured from the nasopharynx of patients with pertussis-like symptoms. To the best of our knowledge, respiratory isolates from Europe have not been characterized. Here, we report the isolation and characterization of B. holmesii from Dutch patients with pertussis-like illness. Species determination was confirmed by 16S rRNA gene sequencing and detection by PCR of IS48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 16 publications
1
16
0
4
Order By: Relevance
“…This pathogenic island may have been acquired from B. pertussis, in which it is involved in the biosynthesis, export and uptake of the alcaligin siderophore in the absence of iron, leading to iron starvation. In microarray studies, Mooi et al [11] reported the presence of this alcaligin operon in the genome of B. holmesii isolated from Dutch patients with pertussis-like illness. This operon (alcABCDERS-fauA) is conserved in the genome of Bho1 and FR4020, and its sequence displays only minor differences with respect to the sequences reported for B. pertussis BP2456 to BP2463.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathogenic island may have been acquired from B. pertussis, in which it is involved in the biosynthesis, export and uptake of the alcaligin siderophore in the absence of iron, leading to iron starvation. In microarray studies, Mooi et al [11] reported the presence of this alcaligin operon in the genome of B. holmesii isolated from Dutch patients with pertussis-like illness. This operon (alcABCDERS-fauA) is conserved in the genome of Bho1 and FR4020, and its sequence displays only minor differences with respect to the sequences reported for B. pertussis BP2456 to BP2463.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a potential problem, because the diagnosis of B. pertussis infection is based on the PCR detection of IS481 sequences. The development of specific PCR diagnosis for B. holmesii infection, targeting the recA gene [7][8][9], or the transposase IS1001bho [10], the amplification of specific target as bhoE [11] or the sequencing of 16sRNA or OmpA [12] has made it possible for a number of retrospective studies to demonstrate an increase in the number of reported cases of respiratory infections due to B. holmesii over the last few years [10,11,[13][14][15][16][17][18][19][20][21]. We wondered whether this increase in detection reflected a real increase in the number of infections or was simply a consequence of the increasing use of RT-PCR targeting IS481 for the diagnosis of B. pertussis since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Although B. pertussis has been classically identified as the sole agent responsible for whooping cough, other species (i.e., B. parapertussis and B. holmesii) can also cause coughing that resembles whooping cough (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). B. pertussis is a Gram-negative, pleomorphic aerobic coccobacillus that grows optimally on either Bordet-Gengou or Regan-Lowe agar between 35°C and 37°C and can be differentiated from other Bordetella species based on its growth and biochemical characteristics.…”
Section: Microbiology Of Bordetella Speciesmentioning
confidence: 99%
“…Although B. parapertussis and B. holmesii have been recognized as causes of whooping cough-like illness, B. parapertussis has been studied more widely than B. holmesii (15,16,28,(33)(34)(35)(36)). Cherry and Seaton analyzed nasopharyngeal specimens submitted for PCR testing from nine states (California, Florida, Illinois, Michigan, New Jersey, Ohio, Texas, Virginia, and Washington) between 2008 and 2010 (27).…”
Section: Microbiology Of Bordetella Speciesmentioning
confidence: 99%
“…In addition to the above-mentioned study and excluding previous and recent reports suggesting that B. holmesii may be an emerging respiratory pathogen which has been isolated from nasopharyngeal specimens of immune-competent patients with pertussis-like symptoms (Njamkepo et al, 2011;Mooi et al, 2011;Mazengia et al, 2000;Yih et al, 1999), we found another 16 case reports (including the present case) of invasive B. holmesii infection. Of the 14 patients for whom data were available, 12 (85 %) were anatomically or functionally asplenic (Njamkepo et al, 2000;Greig et al, 2001;Lam et al, 2008;McCavit et al, 2008;Panagopoulos et al, 2010;Moissenet et al, 2011), one (10 %) had frequently relapsing steroid-sensitive nephritic syndrome (Dörbecker et al, 2007), and one (10 %) was previously healthy (Russell et al, 2001).…”
Section: Discussionmentioning
confidence: 50%